Multicultural Education Solutions for Students - Fiza Raudhoh; Rani Wardani Hasibuan (Yayasan Zia Salsabila, 2024)
Indonesia is a pluralistic and multicultural country, because it has a variety of cultures, ethnicities, tribes, languages, religions, and others. This is a potential that must be developed and developed through education. Multicultural education is the focus in overcoming the challenges of diversity in the current education system. Therefore, this article aims to examine multicultural education solutions that are effective and inclusive by providing equal opportunities for all students to develop according to their abilities, regardless of cultural or ethnic background. The method used in this research is library research, namely by collecting information from various sources of books and journals related to research. The research results obtained a multicultural education solution, namely a comprehensive curriculum approach by integrating material that includes various cultures, values and perspectives, training of teaching staff, involvement of parents and the community and the use of technology. By implementing these solutions comprehensively, it is hoped that multicultural education will create a strong foundation for building a diverse but harmonious society.